Online shoppers vs non-shoppers: A lifestyle study of Malaysian Internet users - Mutum, Dilip; Ghazali, Ezlika (Academy for Global Business Advancement (AGBA), 2006)
This study is among the few to study whether there is any difference in the internet oriented lifestyles between online Malaysian shoppers and non-shoppers. It was found that most online shoppers are young males who were professionals, managers or had their own businesses. They are less concerned about online security, are competent internet users and shop online because they find it fun, easy and convenient. The study also revealed some fundamental satisfied and dissatisfies of shopping online. It is recommended that those companies involved in e-commerce activities should take steps to reduce the fears of the consumers with regards to online shopping.